Photosynthetic aspects and lipid profiles in the mixotrophic alga Neochloris oleoabundans as useful parameters for biodiesel production - Baldisserotto, Costanza (2016)
Fossil fuels will be consumed in few decades, so attention is focused on renewable energy sources, among which microalgae are very promising. Neochloris oleoabundans (Chlorophyta) is one of the most interesting organisms for its capability to accumulate lipids, in particular tryacilglicerols (TAG), useful for biodiesel production, furthermore it can grow mixotrophically. The present work was focused on two basic steps of mixotrophic cultivation with glucose (late exponential -6d- and late stationary -14d- phases of growth), giving attention to relations between photosynthesis and lipid production. Results confirmed that the use of glucose induces a high biomass productivity, which is linked to a rapid replication process until 6d and to enlargement of cells at 14d. At 6d, mixotrophic cells contained numerous stromatic starch grains, while at 14d lipids were highly accumulated and starch tended to reduce. Photosynthetic pigment and protein content decreased under mixotrophy. Photoinhibition following high-light exposure was not significantly affected by mixotrophic cultivation at both experimental times. The creation of a reducing environment due to the photosynthetic activity, together with alterations of N:C ratio, promoted lipid synthesis. Neutral lipids increased under mixotrophy, being oleic acid the major component, while linolenic acid decreased; these aspects fit with requirements for biodiesel production.